DİŞ GELİŞİM BOZUKLUKLARININ GÖRÜLME SIKLIĞININ VE TİPLERİNİN KONİK IŞINLI BİLGİSAYARLI TOMOGRAFİ KULLANARAK BELİRLENMESİ - ÖZDEMİR, ADEM (Fırat Üniveristesi, 2021)
Bu çalışmanın amacı, kliniğe belirli tarihler arasında başvurmuş hasta popülasyonundaki dental anomali varlığını konik ışınlı bilgisayarlı tomografi (KIBT) kullanarak inceleyip, veri toplamak ve anomalilerin yaygınlığını değerlendirmektir. Fırat Üniversitesi Diş Hekimliğ Fakültesi Fakültesi Ağız, Diş ve Çene Radyolojisi Anabilim Dalı'na başvuran 1180 hastadan alınmış KIBT görüntüleri kullanıldı. Diş kaybı bulunmayan, protetik veya endodontik işlem uygulanmamış, periapikal lezyonsuz, kök gelişimi tamamlanmış dişlere sahip hastaların KIBT görüntüleri araştırmada kullanıldı. Yaş ve cinsiyet sınırlaması planlanmadı. KIBT görüntüleri sagital, koronal ve aksiyal düzlemlerde tarandı. İncelenen 1180 hastanın 125(80 kadın, 45 erkek)'inde anomali tespit edildi. Anomali görülen 125 hastada toplam 176 dişte anomali saptandı. Dental anomali sıklığı %10,6 olarak tespit edildi. Kadın ve erkeklere göre dağılımı ise: kadın hastalarda %12, erkek hastalarda %8,72 olarak hesaplandı. Radyografik inceleme sonucu, sırasıyla en çok taurodontizm (%4,1), radix molaris (%3,3), dilaserasyon (%3), dens invajinatus (%0,17) ve füzyon (0,08) tespit edildi. Geminasyona rastlanmadı. Diş hekimleri kök kanal tedavisi sırasında karşılaşabilecekleri dental anomaliler ve bu anomalilerin prevalansları ile ilgili yeterli bilgiye sahip olmalıdır. Kök kanal tedavisi planlanan dental anomaliye sahip bir dişin yanlış tanısı ve tedavisi başarısızlığa neden olabilir. Dental anomali varlığı, dişlerin kök ve kanal yapıları KIBT kullanılarak başarılı bir şekilde tespit edilebilmektedir. Anahtar Kelimeler: dental anomali, endodonti, KIBT

Determination of the incidence and types of tooth development disorders using cone-beam computed tomography Objective: The aim of this study is to examine the presence of dental anomalies in the patient population who applied to the clinic between certain dates, using cone beam computed tomography, to collect data and evaluate the prevalence of anomalies. Materials and Methods: CBCT images taken from 1180 patients who applied to Fırat University Faculty of Dentistry, Department of Oral, Dental and Maxillofacial Radiology were used. CBCT images of patients with no tooth loss, no prosthetic or endodontic procedure, no periapical lesions, and complete root development were used in the study. No age or gender restrictions were planned. CBCT images were scanned in sagittal, coronal and axial planes. Results: Anomaly was detected in 125 (80 female, 45 male) of 1180 patients examined. Anomaly was detected in 176 teeth in total in 125 patients with anomaly. The frequency of dental anomaly was determined as 10,6%. The distribution according to women and men was calculated as 12% in female patients and 8.72% in male patients. As a result of radiographic examination, taurodontism (4,1%), radix molars (3,3%), dileceration (3%), dens invaginatus (0,17%) and fusion (0,08) were detected, respectively. Gemination was not found. Conclusion: Dentists should have sufficient information about the dental anomalies they may encounter during root canal treatment and the prevalence of these anomalies. Misdiagnosis and treatment of a tooth with a dental anomaly for which root canal treatment is planned may lead to failure. The presence of dental anomalies, root and canal structures of the teeth can be successfully detected using CBCT. Keywords: dental anomaly, endodontics, CBCT
Determination of the incidence and types of tooth development disorders using cone-beam computed tomography
Keywords: Diş Hekimliği